2018
DOI: 10.1038/s41598-018-23784-7
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ eye colour sways daughters’ choice of both long- and short-term partners

Abstract: In several species, mate choice is influenced by parental features through sexual imprinting, but in humans evidence is scarce and open to alternative explanations. We examined whether daughters’ preference for mates with light vs dark eyes is affected by the eye colour of parents. In an online study, over one thousand women rated the attractiveness of men as potential partners for either a long- or a short-term relationship. Each male face was shown twice, with light (blue or green) and with dark (brown or da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Replacing maternal with paternal eye colour showed that the light eyes of fathers played no significant role in affecting men's preferences-either on their own or in any interactions, all Fs < 1. These results mirror those found in women: light-eyed male faces looked more attractive to women whose father had light eyes, in both a short-and a long-term context 39 . This symmetry between the sexes also turned up in two separate multiple regressions on men and women's overall preference for light eyes-with own, maternal, and paternal eye colour (light, dark) as independent variables.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Replacing maternal with paternal eye colour showed that the light eyes of fathers played no significant role in affecting men's preferences-either on their own or in any interactions, all Fs < 1. These results mirror those found in women: light-eyed male faces looked more attractive to women whose father had light eyes, in both a short-and a long-term context 39 . This symmetry between the sexes also turned up in two separate multiple regressions on men and women's overall preference for light eyes-with own, maternal, and paternal eye colour (light, dark) as independent variables.…”
Section: Resultssupporting
confidence: 82%
“…Photographs were digitally modified in PortraitPro, creating four versions of each face which differed only in eye colour. As in 39 , these were always shown in pairs ( Fig. 1): blue/dark brown (with blue on the left) and brown/ green (with green on the right).…”
Section: Methodsmentioning
confidence: 67%
See 3 more Smart Citations